A retrospective cohort study of factors influencing long procedure times in colorectal endoscopic submucosal dissection. (3rd October 2021) - Miyaguchi, Kazuya; Tashima, Tomoaki; Terada, Rie; Jinushi, Ryuhei; Nakano, Yuya; Katsuda, Hiromune; Ogawa, Tomoya; Fujita, Akashi; Tanisaka, Yuki; Mizuide, Masafumi; Mashimo, Yumi; Nakamoto, Hidetomo; et al.
Abstract: Objective: To evaluate the outcomes and factors influencing colorectal endoscopic submucosal dissection (ESD) with a long procedure time. Materials and methods: In this single-center, retrospective study, we included 1, 100 patients with 1, 199 lesions who underwent colorectal ESD between April 2016 and December 2020. ESD was performed using an advanced system knife for lesions >20 mm. An S-O clip was used as the traction device. The long-time group (LP; procedure time >120 min) and normal-time group (NP; procedure time <120 min) were compared. Results: The procedure times were 166.86 and 44.72 min in the LP and NP groups, respectively. The completion rate was higher in the NP group (96.5% vs. 83.5%, p  = .001); the completed lesions were resected en bloc. Multivariate analysis revealed 18.8% and 7.8% of submucosal fibrosis in the LP and NP groups, respectively (odds ratio [OR] = 2.410, p  = .026). Compared to the NP group, the LP group presented larger maximum lesion sizes and higher rates of R1 resection, and traction device use. Time to introduction of traction device use was longer in the LP than in the NP group (126.05 vs. 21.72 min; p  < .001). Fibrosis tends to occur cecal lesions (OR 2.436, p  = .011) and laterally spreading tumor–non-granular-pseudo-depressed (LST-NG-PD) (OR 2.6181, p  = .001). Conclusions: Lesion size and fibrosis were factors associated with a long procedure time in colonic ESD. For fibrotic lesions (LST-NG-PD and cecal lesions), it is necessary to consider early use of traction devices and advisable to plan a strategy for the use of traction devices.